Rapamycin Nano-Micelle Ophthalmic Solution Reduces Corneal Allograft Rejection by Potentiating Myeloid-Derived Suppressor Cells' Function - Wei, Chao; Wang, Yuexin; Ma, Li; Wang, Xin; Chi, Hao; Zhang, Sai; Liu, Ting; Li, Zhiyuan; Xiang, Demeng; Dong, Yanling; Wu, Xianggen; Shi, Weiyun; et al. (Frontiers in Immunology, 2018)
Allograft rejection is the major cause for corneal graft failure. Rapamycin（RAPA）was reported as an effective and novel immunosuppressive agent for patients undergoing corneal transplantation. However, the high water insolubility and low bioavailability has strongly constrained its clinical application. Here we successfully developed RAPA nano-micelle ophthalmic solution, and found that corneal allograft survival in RAPA nano-micelle ophthalmic solution treated recipients was significantly prolonged for more than 2 months, with less inflammatory infiltration, decreased production of pro-inflammatory factors and elevated recruitment of MDSCs. MDSCs from RAPA nano-micelle ophthalmic solution treated mice could significantly inhibit the proliferation of CD4+T cells with increased expressions of inducible nitric oxidase (iNOS) and arginase-1 (Arg-1). Activity blockade of Arg-1 and iNOS pharmacologically reversed their immunosuppressive ability. Moreover, the effects of RAPA were counterbalanced by the administration of anti-Gr-1 antibody or inhibiting the activity of iNOS pharmacologically. In addition, RAPA nano-micelle also effectively alleviated the allograft rejection in high-risk rabbit PKP models with corneal vascularization. Collectively, our results demonstrated that RAPA nano-micelle ophthalmic solution could improve the immunosuppressive activity of MDSCs through elevated expression of Arg-1 and iNOS, which highlights the possible therapeutic applications of RAPA on corneal allograft rejection.